Grain growth and recrystallization behaviors of an ultrafine grained Al-0.6 wt%Mg-0.4 wt%Si-5vol.%SiC nanocomposite during heat treatment and extrusion - Yao, X.; Zheng, Y.; Quadir, Md Zakaria; Kong, C.; Liang, J.; Chen, Y.; Munroe, P.; Zhang, D. (Elsevier B.V., 2018)
A bulk ultrafine grained Al-0.6 wt%Mg-0.4 wt%Si-5vol.%SiC nanocomposite was fabricated by spark plasma sintering (SPS) of a corresponding nanocrystalline metal matrix nanocomposite powder produced by high energy mechanical milling. The as-SPSed samples were either heat treated or hot extruded at 500 °C. Microstructural characterization of the samples revealed that the ultrafine Al(Mg,Si) grains in the as-SPSed sample grew slightly and underwent recovery during heat treatment, and dynamic recrystallization, rapid grain growth and grain boundary dragging of SiC nanoparticles occurred during extrusion. The Al(Mg,Si) grain growth and grain boundary dragging of the SiC nanoparticles during extrusion resulted in aggregation of a large fraction of the SiC nanoparticles which in turn caused formation of regions with finer and coarser Al(Mg, Si) grains respectively.